The attitudes about life-sustaining treatment among cardiac surgery ICU patients and their families - Sun, Si; Zhang, Hao; Xiong, XiaoYan (Frontiers in Surgery, 2023)
Purpose To investigate the attitudes among cardiac surgery ICU patients and their families regarding life-sustaining treatment. Methods A total of 172 pairs of patients in the cardiac surgery ICU of Nanjing First Hospital and their family members were enrolled in this study that examined their attitudes toward life-sustaining treatment using a willingness to care for life-sustaining treatment questionnaire. The consistency of the attitudes of patients and family members toward life-sustaining treatment was analyzed by the chi-square test with a paired design. Results The most popular life-sustaining treatment for cardiac ICU patients was noninvasive mechanical ventilation (79.1%); the most unpopular was intra-aortic balloon counterpulsation (48.3%). Most patients and their families had not considered electric defibrillation (65.7%), but most understood and were willing to permit cardiopulmonary resuscitation (76.2%). Few family members agreed that patients should receive a pacemaker (25.0%). The consistency of life support attitudes of patients and their families ranged from 12.8% to 60.5% for procedures both would agree to, 1.2% to 19.8% for procedures they were unwilling to permit, and 0.6% to 39.0% for procedures they had not considered. Kappa values ranged from 0.218 to 0.597 (P < 0.05), with general consistency. Conclusion Cardiac surgery ICU patients families are generally consistent in their attitudes toward life-sustaining treatment, and family members’ choices are not representative of patients’ wishes.